The new genus Pheude (Coleoptera, Curculionidae, Cossoninae) with description of a new species from mainland China - Youssef M. Omar; Runzhi Zhang; Steve R. Davis (ZooKeys, 2014)
A new weevil, Pheude punctatus gen. et sp. n., of the tribe Dryotribini in Cossoninae, is described from Guangdong Province, South China. It differs from the related genera Dryotribus Horn and Microtribodes Morimoto in having antennae with seven articles and a distinct scutellum, and from Ochronanus Pascoe and Stenomimus Wollaston in having long antennae, a rostrum with a medio-longitudinal furrow beginning at the posterior margin of the eyes and extending approximately midway on the rostrum, and a moderately elevated, medio-longitudinal carina extending the full length of the pronotum. Other diagnostic characters and illustrations are provided. A key to the genera of Dryotribini known from China is given.